PENDIDIKAN PROFETIK: TELAAH POLA DAN KONSEP PENDIDIKAN NABI MUHAMMAD SAW - Indriyani , Maulida; Maryam, St.; Umam, Khoirul (Cognitive: Jurnal Pendidikan dan Pembelajaran, 2025)
Through various life experiences that include moral, social, and spiritual education, the Prophet Muhammad's education provides in-depth knowledge about character and intellectual formation. This research uses a descriptive qualitative method with a literature approach and analyzes various primary and secondary sources about the Prophet's life to learn how he was educated, from childhood to adulthood, and how it has influenced the modern education system. This education builds loyal, responsible, and moral characters. A holistic approach to character, such as the habituation of moral values, dialogic, and deliberation, is important for the modern education system. In short, the education taught by the Prophet Muhammad can serve as an ideal model for building individuals who excel spiritually, morally, and intellectually. This method offers a solution to the moral crisis occurring in the modern education system.